2019
DOI: 10.19126/suje.463610
|View full text |Cite
|
Sign up to set email alerts
|

4- 6 yaş çocuklarının Davranış Düzenleme Becerileri ile Ses Bilgisel Farkındalık, Görsel Eşleştirme ve Yazı Yazma Öncesi Becerileri Arasındaki İlişkinin İncelenmesi

Abstract: Behavior regulation skills are associated with early academic skills in pre-school children in the studies. In addition to this, limited number of studies has been shown relations between behavioral regulation skills and early literacy skills; phonological awareness, matching images and pre-writing skills. The study aims at assessing the relation between phonological awareness, matching images and pre-writing skills which are early literacy skills and behavior regulation skills in preschool children with regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
(38 reference statements)
0
2
0
1
Order By: Relevance
“…Berdasarkan penelitian (Mohammed & Al-Noori, 2020) menyatakan kemampuan menulis anak akan berkembang dengan brainstorming dimana akan membantu anak mengembangkan ide tulisan. Adanya relevansi antara keterampilan menulis dengan kesadaran fonologis (Yalçıntaş sezgin et al, 2019). Sudut pandang berbeda tentang gender membuktikan bahwa identifikasi keterampilan menulis anak perempuan lebih baik disbanding anak laki-laki (Adams & Simmons, 2019).…”
Section: Pendahuluanunclassified
“…Berdasarkan penelitian (Mohammed & Al-Noori, 2020) menyatakan kemampuan menulis anak akan berkembang dengan brainstorming dimana akan membantu anak mengembangkan ide tulisan. Adanya relevansi antara keterampilan menulis dengan kesadaran fonologis (Yalçıntaş sezgin et al, 2019). Sudut pandang berbeda tentang gender membuktikan bahwa identifikasi keterampilan menulis anak perempuan lebih baik disbanding anak laki-laki (Adams & Simmons, 2019).…”
Section: Pendahuluanunclassified
“…To determine children's behaviour regulation skills, the "Head-Toes-Knees-Shoulders" (HTKS) Task Measurement Tool, which was developed by Ponitz et al (2009) and whose Turkish validity and reliability study was carried out by Sezgin and Demiriz (2015), was used. This measurement tool has strong reliability (Ponitz et al, 2009;Matthews, Marulis, & Williford, 2014;Montroy, Bowles, Skibbe, & Foster, 2014;Yalçıntaş-Sezgin, Ulus, & Şahin, 2019;Wanless et al, 2011). It is an easy-to-use self-regulation measurement tool.…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…Several researchers have tested the reliability of the HTKS, and the data show strong psychometric properties with little variability across studies, including coefficient alpha, test–retest reliability, and interrater reliability (Cameron et al, 2012 ; McClelland et al, 2014 ; Lipsey et al, 2017 ; Zhang and Rao, 2017 ; Hee et al, 2018 ; Liu et al, 2018 ; Spiegel and Lonigan, 2018 ; Cerino et al, 2019 ; Sezgin et al, 2019 ). Some studies have also found the HTKS predictive of academic outcomes and significantly related to children's working memory, attentional flexibility, and inhibitory control (Cameron Ponitz et al, 2008 , 2009 ; Gestsdottir et al, 2014 ; McClelland et al, 2014 , 2021 ; Schmitt et al, 2014 , 2017 ; Fuhs et al, 2015 ; Lipsey et al, 2017 ; Hee et al, 2018 ; Gonzales et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%